A Novel Decision Aid for Surgical Patients with Ulcerative Colitis: Results of a Pilot Study. Issue 6 (June 2016) - Cohan, Jessica N.; Ozanne, Elissa M.; Sewell, Justin L.; Hofer, Rebecca K.; Mahadevan, Uma; Varma, Madhulika G.; Finlayson, Emily
Abstract : BACKGROUND: Up to 30% of patients who have ulcerative colitis are faced with the complex decision between end ileostomy and IPAA. We developed a decision aid to encourage shared decision making between patients and surgeons. OBJECTIVE: The aim of this study is to determine whether a decision aid is effective and acceptable for surgical patients with ulcerative colitis and their treating surgeons. DESIGN: This was a prospective cohort study. SETTINGS: Patients and surgeons were enrolled from 3 colorectal surgery clinics. PATIENTS: Consecutive adult patients with ulcerative colitis who were candidates for IPAA and end ileostomy were selected. INTERVENTIONS: Patients used a multilingual decision aid before meeting with the surgeon. MAIN OUTCOME MEASURES: We measured changes in knowledge, treatment preference, and stage of decision making, as well as preparation for decision making, patient satisfaction, and surgeon satisfaction after using the decision aid. RESULTS: Twenty-five patients were enrolled; 5 had previously undergone subtotal colectomy. After using the decision aid, patients' knowledge scores improved by 39% ( p < 0.006), 6 patients changed their treatment preference, and 8 reported increased certainty in treatment preference. The median for preparation for decision making was 75 of 100. Patient satisfaction with the decision aid (median score, 37/41) and surgeon satisfaction with the clinical encounter (median score, 38/45) were high. Patients who previously underwent subtotal colectomy had lower preparation for decision-making scores (median score, 58 vs 78 for surgery-naïve patients, p = 0.06), and did not report increased certainty in treatment preference after using the decision aid. LIMITATIONS: The study included a small sample with no comparison group. CONCLUSIONS: A novel decision aid for surgical patients with ulcerative colitis appears to be effective and acceptable in patients and surgeons from diverse clinical settings. Patients who have not yet initiated surgical treatment seem to benefit most. Future studies to validate the knowledge questionnaire and test the decision aid in a randomized fashion are warranted. Abstract : Supplemental Digital Content is available in the text.